Fuzzy Multi-criteria Decision Making associated with Risk and Confidence Attributes - Chandrashekhar Meshram; Shyam Sundar Agrawal (Bulletin of Electrical Engineering and Informatics, 2015)
The multicriteria decision problems involve uncertainty, it is important to incorporate different types of uncertainty in any proposed solution. In this paper, we presented fuzzy MCDM approach based on risk and confidence analysis that we believe is effective in tackling complex, ill-defined and human-oriented decision problems.